2003
DOI: 10.1016/s0955-2219(02)00286-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes prepared in situ in a cellular ceramic by the gelcasting-foam method

Abstract: International audienceThe synthesis of carbon nanotubes from an oxide solid solution foam is reported for the first time. A foam of Mg0.9Co0.1Al2O4 solid solution is prepared by the gelcasting-foam method using notably mono- and di-functional acrylate monomers. Using a surfactant in the alkylpolyglucoside family allows to prevent structure changes in the foam before the onset of polymerisation. The wet ceramic foam is dried in air, producing a foam with an open porosity. Total porosity is equal to about 98% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…26,29 This is the consequence of an easier supply of the H 2 -CH 4 gas mixture to the catalytic material. We used several Mg 1−x Co x Al 2 O 4 powders (containing or not some MoO x oxide), which were attritor milled, the products being then only partly evaporated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,29 This is the consequence of an easier supply of the H 2 -CH 4 gas mixture to the catalytic material. We used several Mg 1−x Co x Al 2 O 4 powders (containing or not some MoO x oxide), which were attritor milled, the products being then only partly evaporated.…”
Section: Methodsmentioning
confidence: 99%
“…The gelcasting-foam method was described in detail elsewhere. 29 By reduction of the IF and GF foams, a series of other CNT-metal-MgAl 2 O 4 composites (C5, C6, CM4-CM9; Table 1) were obtained containing more CNT than those obtained by reduction of the corresponding catalytic materials in the form of powder beds.…”
Section: Methodsmentioning
confidence: 99%
“…Both ceramic honeycombs and ceramic foams have been used as substrates on which different types of 1D nanostructures were created, using different approaches. These include carbon nanofibers (CNFs), [5][6][7][8][9][10][11][12][13] carbon nanotubes (CNTs), [14][15][16][17][18][19][20] or SiC nanofibers. 4,21 Previous works demonstrated that moderate (B30 m 2 /g) to high (B150 m 2 /g) values for the SSA could be obtained, depending on the amount, length, and diameter of the nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to form nanotubes inside preexisting porous matrices. Rul et al formed a porous spinel structure with gel casting [9]. This matrix also contained a small amount of Co catalyst, and subsequent CVD produced a relatively high nanotube volume fraction inside the porous oxide.…”
Section: Processing and Properties Of Cnt Reinforced Compositesmentioning
confidence: 99%